PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG DAN PERPUTARAN MODAL KERJA TERHADAP RENTABILITAS PADA PT PELAYARAN SINAR MANDIRI SEJAHTERA KOTA BATAM - Dian Efriyenti (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
This study aims to determine whether the effect of cash turnover, turnover of receivables and working capital turnover affect the profitability on a cruise PT Sinar Mandiri Sejahtera Batam. Results from the study showed that the velocity of cash (X1) but not significant effect on return on equity with significant value 0,714> 0,05, receivables turnover (X2) effect on return on equity with significant value 0,010 <0,05, working capital turnover (X3) but no significant effect on return on equity with significant value 0,653> 0,05. Cash turnover, turnover of receivables and working capital turnover significant effect simultaneously (together) to variable return on equity. The test results demonstrate the value of 15,360 F count> F table 2,77 with a significance value of 0.000. Judging from the significant value that is less than 0,05 means the (H4) is accepted. Keywords: Turnover Cash, Accounts Receivable Turnover, Turnover Of Working Capital, Profitability.